Behavioral Accounting Review For Non-Performing Customer Reporting : Case Baitul Maal Wattamwil - Putri, Della Sabrina Indah; Murniati Mukhlisin; Mohammad Hudaib (Universitas Muhammadiyah Surakarta, 2024)
The challenge of BMT development is the elevated Non-Performing Financing (NPF) level. This study aims to investigate how BMT addresses this NPF challenge by utilizing interview techniques and conducting content analysis through qualitative methods, all from a behavioral accounting perspective. The specific BMT under examination operates within the West Java region. The research findings reveal that measures have been taken to prevent the occurrence of high Non-Performing Loans (NPLs), and the roles played by BMT's management and accountants in reporting have been instrumental, particularly in decision-making. The NPF Customer reporting is a form of BMT management responsibility to stakeholders. An intriguing discovery is that BMT must effectively leverage its social functions to mitigate the risk of high NPF.